2019
DOI: 10.1177/0363546519843070
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Labral Repairs of the Shoulder Among Baseball Players: Results and Outcomes With Minimum 2-Year Follow-up

Abstract: Background: There is a paucity of information regarding the treatment of posterior labral tears of the shoulder for baseball players. Reports regarding treatment and postoperative outcomes are more limited than its anterior and superior counterparts. Purpose: To evaluate the clinical presentation, surgical findings, postoperative outcomes, and rate of return to sport after arthroscopic repair of posterior labral injuries of the shoulder among baseball players. Study Design: Case series; Level of evidence, 4. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 40 publications
(65 reference statements)
1
45
0
1
Order By: Relevance
“…Pennington et al 23 found an overall RTS rate of 93% for those who underwent revision and 82% for those who did not, without any limitations in all athletes. Kercher et al 15 found a RTS rate of 94% at any level and 61% at the same level. However, pitchers had a RTS rate at the same level of 41%, which was lower than that of nonpitchers.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Pennington et al 23 found an overall RTS rate of 93% for those who underwent revision and 82% for those who did not, without any limitations in all athletes. Kercher et al 15 found a RTS rate of 94% at any level and 61% at the same level. However, pitchers had a RTS rate at the same level of 41%, which was lower than that of nonpitchers.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study of throwing athletes only, the rate of revision was 8.6%. The demands of the throwing motion produce a tremendous amount of force on the shoulder, 14,15,17 and the stress from repeated throwing motions may lead to tensile failure of the posterior capsulolabral complex, which may account for the revision rate. Furthermore, as for superior labrum anterior-posterior (SLAP) repairs, RTS after surgery of the labrum for throwers is very challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This systematic review demonstrated that RTP was achievable at a high rate after posterior shoulder stabilization. 9,18,19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Bradley et al 28 evaluated 200 shoulders, diagnosed with unidirectional recurrent posterior shoulder instability, and noted that 90% returned to play. Both McClincy et al 38 and Radkowski et al 40 compared surgical outcomes and RTP rates in throwing and nonthrowing athletes.…”
Section: Discussionmentioning
confidence: 99%
“…However, pitchers were less likely than position players to return to preinjury levels (41% versus 86%). 35 This suggests that it may be harder to return to certain positions in baseball and potentially other major sports after PSI.…”
Section: Discussionmentioning
confidence: 99%